Adobe Flash-based Edutainment Media: is it suitable for learning math? - Indah Sari, Tri Hariyati Nur Indah Sari; Lestari, Wiwit Damayanti (Insitut Agama Islam Negeri Kerinci, 2023)
Since information and communication technology (ICT) is developing so fast in today's digital era, it is important to create learning materials that can be accessed through various digital devices. The purpose of this research is to create edutainment media that can be applied for arithmetic learning. This research uses the Borg and Gall (R&D) development model which is limited to several stages. These stages are: a) information gathering; b) planning; c) product manufacturing; and d) validation and testing. The questionnaire was the research instrument. A total of 34 students who were the test subjects as well as material and media validators were sent questionnaires. Descriptive quantitative analysis was used for data analysis. Validation of Adobe Flash-based math learning media by material experts resulted in an overall score of 78.7%, including the criteria of